The impact of value co-creation on consumer citizenship behavior: Based on consumer perspective - Yang, Jialiang; Ren, Jifan; Zhao, Meihui; Chen, Haoyu; Wang, Huihan (Frontiers in Psychology, 2023)
This research investigated the value co-creation mechanism in livestreaming platforms and the internal mechanism of user value co-creation behavior on the short video platform Tik Tok, and supplements the literature on value co-creation in livestreaming shows. We also examined the internal mechanism of the perceived value between engagement behavior and citizenship behavior. The results indicated that user-perceived value mediated the relationship between user engagement and citizenship behaviors. In addition, short video platforms exhibit significant community attributes, and interactive behavior is the primary user engagement that enhances the perceived value produced. Users join short video platforms often out of interest, looking for communities that interest them. Users' responses generate the perceived value. Thus, it enhances users' intentions to continue using a particular service, thus increasing the likelihood of citizenship behavior. We also found that users' creative behavior in short video platforms tends to concentrate on social and functional values. Thus, users of livestreaming and short video platforms such as Tik Tok seek social recognition by sharing their opinions or daily lives. The investigation of perceived value mediating the relationship between user engagement behavior and citizenship behavior revealed that perceived value significantly mediated the relationship between user engagement behavior and citizenship behavior. To gain the recognition of others, users often actively participate in the platform by uploading their works and sharing their creations, which generate significant social impact. The results also reveal the outstanding co-creation in citizenship behavior. First, Tik Tok's users are deeply engaged in the platform and their cognitive messages are integrated into the platform through interacting with other users, browsing and creating short videos. Second, Tik Tok provides a high level of interactivity, thus facilitating social interaction among strangers. Video uploaders and fans develop positive interactive relationships. Third, Tik Tok viewers may become video providers at some point. For video providers, Tik Tok offers a simple function, as it mainly deals with 15-second short videos. The act of co-creation creates economic value for the platform and generates emotional, functional and social values for its users.